Long-term degradation of resin-based cements in substances present in the oral environment: influence of activation mode - Eduardo Moreira da SILVA; Jaime Dutra NORONHA-FILHO; Cristiane Mariote AMARAL; Laiza Tatiana POSKUS; Jose Guilherme Antunes GUIMARAES (University of São Paulo, 2013)
Indirect restorations in contact with free gingival margins or principally within the gingival sulcus, where the presence of organic acids produced by oral biofilm is higher, may present faster degradation of the resin-based cement pellicle. Objectives To investigate the degradation of four resin-based cements: Rely X ARC (R), Variolink II (V), Enforce (E) and All Cem (A), after immersion in distilled water (DW), lactic acid (LA) and artificial saliva (AS) and to analyze the influence of the activation mode on this response. Material and Methods Two activation modes were evaluated: chemical (Ch) and dual (D). In the dual activation, a two-millimeter thick ceramic disk (IPS Empress System) was interposed between the specimen and light-curing unit tip. Specimens were desiccated, immersed in distilled water, artificial saliva and lactic acid 0.1 M at 37°C for 180 days, weighed daily for the first 7 days, and after 14, 21, 28, 90 and 180 days and were desiccated again. Sorption and solubility (µg/mm 3 ) were calculated based on ISO 4049. The data were submitted to multifactor analysis of variance (MANOVA) and Tukey's HSD test for media comparisons (α=0.05). Results Sorption was higher after immersion in LA (p<0.05) and increased significantly with time (p<0.05). Sorption was influenced by the activation mode: Ch>D (p<0.05). The lowest solubility was presented by R (p<0.05). Conclusions Lactic acid increased the degradation of resin-based cements. Moreover, the physical component of activation, i.e., light-activation, contributed to a low degradation of resin-based cements.